Pengembangan Media Pembelajaran Menggambar Teknik Untuk Mahasiswa Berbasis Android - Satrio Ajie Minarto; I Wayan Sugita; Ahmad Kholil (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
This research aims to develop Engineering drawing learning media for students based on Android using Adobe Flash Professional CS6 software. The development method used in this research is Research and Development (R&D) with the ADDIE development model, The stages are: Analysis, Design, Development, Implementation, and Evaluation. The method used in data collection is using a questionnaire. In the material validation trial, the learning media got a percentage score of 80% and was included in the